2019
DOI: 10.1080/00480169.2019.1596523
|View full text |Cite
|
Sign up to set email alerts
|

Investigating associations between lamb survival to weaning and dam udder and teat scores

Abstract: Aims: To examine a range of udder and teat traits in Romney ewes and to describe the frequency with which different scores occur, and to investigate associations between lamb survival to weaning and ewe udder and teat scores. Methods: Mixed-age, mature Romney ewes (n = 1,009) were enrolled from a commercial sheep flock located in the Wellington region of New Zealand in January 2017. A range of udder and teat traits were scored in all ewes, using visual assessment and palpation, at pre-mating (February), pre-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 14 publications
3
33
3
Order By: Relevance
“…However these relationships varied between traits and management times. Similarly, we found that the relationship between lamb survival and udder and teat scores varied between traits and management times (Griffiths et al 2019).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…However these relationships varied between traits and management times. Similarly, we found that the relationship between lamb survival and udder and teat scores varied between traits and management times (Griffiths et al 2019).…”
Section: Discussionsupporting
confidence: 57%
“…If farmers wish to identify ewes whose lambs are predicted to have poorer performance, the results of the present study indicate pre-mating udder palpation score would be an appropriate trait to assess. When combined with the results of our analysis of traits associated with lamb survival (Griffiths et al 2019), these results indicate that offspring of ewes with premating udder palpation scores of hard have greater odds of failure to survive to weaning, and, should they survive, have lower growth rates to weaning compared with offspring whose dams had normal udder palpation scores.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations